Preparation of Ti-doped lamellar FER molecular sieve and application of Ti-doped lamellar FER molecular sieve in rutin electrochemical sensing detector
By using carbon chain organic compound template agent to prepare titanium-doped sheet FER molecular sieve and solid-loaded chitosan composites to modify the electrode, the problem of insufficient detection sensitivity of existing electrochemical sensors to rutin is solved, and a wider linear range of detection concentration and a lower detection lower limit is achieved.
Patent Information
- Application Number
- CN202411755279.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-03
AI Technical Summary
The linear range of concentrations of existing electrochemical sensors for rutin detection is narrow, which may not be able to cover the detection requirements of low rutin states, and its detection sensitivity needs to be further improved.
Using carbon chain organic compounds as template agents, in the preparation of titanium-doped sheet FER molecular sieve, a material with a high specific surface area and multiple catalytic sites was prepared by hydrothermal method, and the electrodes were modified by solid-supported chitosan composite material to improve the electrocatalytic oxidation capacity of rutin.
The sensitivity and selectivity of rutin detection are significantly improved, and the linear range of detection concentration is expanded to 0.1-10 μmol/L, the lower detection limit is low, the stability is good, and the repeatability and selectivity are high.
Smart Images

Figure CN119661382A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of molecular sieve synthesis technology and electrochemical sensor detection technology, and specifically to the preparation of a Ti-doped lamella FER molecular sieve and its application in a rutin electrochemical sensor detector. Background Art
[0002] Rutin (RUT), also known as vitamin P, is a common polyphenol flavonoid. The human body cannot synthesize rutin by itself and must be ingested from food. It is mainly derived from apricots, dates, cherries, orange peels, and citrus ingredients, and is particularly rich in Sophora japonica rice and buckwheat flowers. Because of its significant biological and pharmacological activities, it is widely used in the health care system. Usually, rutin is used as an antioxidant and nutritional enhancer in human daily life. At the same time, it also has a good inhibitory effect on some human diseases, showing anti-tumor, anti-hypertension, antibacterial, antiviral and anti-edema properties. In particular, it can effectively regulate the osmotic pressure of capillaries and stabilize platelets. However, excessive intake of rutin can lead to central nervous system depression, gastrointestinal bleeding, and renal damage. Therefore, the quantitative analysis of rutin in food and medicine is of great significance in food and drug control.
[0003] At present, the methods for detecting rutin include spectroscopy, chromatography, electrochemistry, etc. Some commonly used analytical methods, such as high performance liquid chromatography, capillary electrophoresis and spectrophotometry, have been used for the determination of rutin. However, some of these methods are time-consuming, costly or require complex pretreatment processes, which hinders their further application. Electrochemical analysis is a type of instrumental analysis method based on the electrochemical properties of substances in solution. According to the electrochemical properties of substances in solution and their changing laws, it is based on the relationship between electrical quantities such as potential, conductivity, current and charge and certain quantities of the measured substance to conduct qualitative and quantitative instrumental analysis of components. Compared with these methods, electrochemical determination has the advantages of good reliability, fast response, cheap instruments, low energy consumption, simple operation, time saving, high sensitivity, strong selectivity, etc., especially its equipment is easy to carry and can be measured on site. In recent years, with the development of nanoscience and nanotechnology, many nanomaterial electrodes that can significantly improve the signal strength of electrochemical sensors and achieve ultra-sensitive determination have been applied to the electrochemical determination of rutin.
[0004] Arvand et al. (Arvand. A new electrochemical sensing platform based on binary composite of graphene oxide-chitosan for sensitive rutin determination. Food Analytical Methods 10 (2017): 2332-2345.) disclose a novel electrochemical sensor based on graphene oxide-chitosan binary complex and for sensitive determination of rutin, the concentration linear range reaches 0.9~90 μmol / L, and the detection limit reaches 0.56 μmol / L. However, the electrochemical sensor obtained by the above-mentioned prior art has a higher detection limit for rutin, and may not cover the detection requirements in some special cases (such as low rutin state), and its detection sensitivity needs to be further improved. Summary of the invention
[0005] In order to solve the problem that the concentration linear range of existing electrochemical sensors for rutin detection is still narrow and may not cover the detection requirements in certain special cases (such as low rutin state), and its detection sensitivity needs to be further improved, the primary purpose of the present invention is to provide a carbon chain organic compound.
[0006] Another object of the present invention is to provide use of the organic compound in preparing FER molecular sieve.
[0007] Another object of the present invention is to provide a titanium-doped lamellar FER molecular sieve.
[0008] Another object of the present invention is to provide a titanium-doped lamellar FER molecular sieve immobilized chitosan composite material.
[0009] Another object of the present invention is to provide an electrochemical sensor.
[0010] Another object of the present invention is to provide a three-electrode system.
[0011] Another object of the present invention is to provide the use of the titanium-doped lamella FER molecular sieve or the titanium-doped lamella FER molecular sieve immobilized chitosan composite material or the electrochemical sensor or the three-electrode system in detecting rutin.
[0012] The purpose of the present invention is achieved through the following technical methods:
[0013] A carbon chain organic compound, the structural formula of the organic compound is: NH2-C2H4-NH-(CH2) n -O-(p-C6H4)2-O-(CH2) n-NH-C2H4-NH2; wherein n is 10 to 16.
[0014] The carbon chain organic compound designed in the present invention serves as a template agent and plays a role in structure guidance and pore filling in the preparation of FER molecular sieves. The special long carbon chain guides the lamellar structure of the Na-FER molecular sieve, so that the FER molecular sieve has a smaller crystal structure. Micropores and mesopores are generated simultaneously during the preparation process, which greatly increases the specific surface area of the molecular sieve, improves the adsorption effect of the molecular sieve on rutin, and exposes more active sites of the molecular sieve, which is conducive to the electrocatalytic reaction of rutin on the sensor.
[0015] In the present invention, the carbon chain organic compound is used as a template agent, and the template agent can regulate the synthesis of the layered FER molecular sieve. The FER molecular sieve in the present invention is mainly used as a catalyst to adsorb rutin molecules and catalyze the electrocatalytic reaction. In addition, the layered FER molecular sieve obtained by the present invention is a material with a high specific surface area, more catalytic sites, a large adsorption capacity and excellent molecular mass transfer and diffusion performance, and has a wide range of applications in catalysis and adsorption.
[0016] Due to the weak conductivity of the lamellar FER molecular sieve, the electrochemical response in electrochemical catalysis is very weak, the detected oxidation peak is not obvious, the sensitivity is poor, and it cannot be used directly to detect rutin. Therefore, the FER molecular sieve is doped with titanium to give it a certain electrocatalytic oxidation ability for rutin. The introduction of titanium enhances the conductivity of the molecular sieve, exposes more active sites of the molecular sieve, and enhances the catalytic performance of the molecular sieve. In addition, the modification by doping with metal ions does not basically change its original morphology and pore structure.
[0017] The preparation process of the carbon chain organic compound comprises: performing a reaction of 4,4-biphenol and a halogenated long-chain alkane in an inert gas to obtain a precursor, and performing a reaction of the precursor and ethylenediamine to obtain the carbon chain organic compound.
[0018] Specifically, the structural formula of the precursor is: X-(CH2) n -O-(p-C6H4)2-O-(CH2) n -X; wherein n is 10 to 16, and X is one of Cl, I, and Br.
[0019] Specifically, the halogenated long-chain alkane is one of 1,10-dibromodecane, 1,12-dibromododecane, and 1,16-dibromohexadecane.
[0020] Preferably, the halogenated long-chain alkane is 1,12-dibromododecane.
[0021] Preferably, the structural formula of the carbon chain organic compound is:
[0022] NH2-C2H4-NH-(CH2) 12 -O-(p-C6H4)2-O-(CH2) 12 -NH-C2H4-NH2.
[0023] The present invention also protects the application of the template in the preparation of FER molecular sieve.
[0024] A titanium-doped lamellae FER molecular sieve is prepared by a hydrothermal method using the organic compound as a template.
[0025] Specifically, the method for preparing the titanium-doped lamellae FER molecular sieve comprises the following steps:
[0026] S1. Mixing an aluminum source, an alkali source, a silicon source, a template and water to obtain an aluminosilicate gel;
[0027] S2. mixing the aluminosilicate gel with a titanium source, hydrothermally heating, and calcining to obtain the titanium-doped lamellar FER molecular sieve;
[0028] The mass ratio of the titanium source to the aluminosilicate gel is 1:100-500.
[0029] Preferably, the mass ratio of the titanium source to the aluminosilicate gel is 1:200.
[0030] Specifically, the molar ratio of the aluminum source, the alkali source, the silicon source, the template and water is 1: (0.4-20): (1-40): (0.02-6): (20-800).
[0031] Preferably, the molar ratio of the aluminum source, the alkali source, the silicon source, the template and water is 1: (0.4-10): (4-20): (0.1-1.5): (100-400).
[0032] More preferably, the molar ratio of the aluminum source, the alkali source, the silicon source, the template and water is 1:(0.5-1):(5-10):(0.2-1):(200-300).
[0033] Specifically, the hydrothermal temperature is 130-200°C.
[0034] Specifically, the hydrothermal time is 230 to 250 hours.
[0035] Specifically, the calcination temperature is 450-650°C.
[0036] Specifically, the calcination time is 4 to 6 hours.
[0037] Specifically, the aluminum source is at least one of sodium aluminate, aluminum sulfate, and boehmite.
[0038] Preferably, the aluminum source is sodium aluminate.
[0039] Specifically, the alkali source is at least one of sodium hydroxide, potassium hydroxide and lithium hydroxide.
[0040] The alkali source is used to adjust the alkalinity of the reaction system and promote the formation of aluminosilicate.
[0041] Preferably, the alkali source is sodium hydroxide.
[0042] Specifically, the silicon source is at least one of silica sol, white carbon black, sodium silicate and ethyl orthosilicate.
[0043] Preferably, the silicon source is silica sol.
[0044] The present invention uses silica sol as the silicon source. Silica sol is easy to precipitate crystals under hydrothermal conditions, which can improve the crystallinity of the FER molecular sieve, thereby improving the acid and heat resistance and stability of the molecular sieve.
[0045] Specifically, after hydrothermal treatment, the obtained product needs to be post-treated.
[0046] More specifically, the post-treatment includes centrifugation and washing.
[0047] More specifically, the centrifugation is performed at 6000-10000 r / min for 1-5 min.
[0048] Specifically, the titanium source is at least one of titanium dioxide, titanium sulfate and titanium nitrate.
[0049] Preferably, the titanium source is titanium dioxide.
[0050] A titanium-doped lamellar FER molecular sieve immobilized chitosan composite material, the preparation method of which comprises the following steps:
[0051] The titanium-doped lamella FER molecular sieve is dispersed in an aqueous solution of acetic acid and chitosan to obtain the titanium-doped lamella FER molecular sieve immobilized chitosan composite material.
[0052] Specifically, the mass ratio of the titanium-doped lamellar FER molecular sieve, chitosan, acetic acid and water is 1: (0.6-1.5): (0.1-0.6): (600-1500).
[0053] An electrochemical sensor comprises an electrode and the titanium-doped sheet FER molecular sieve immobilized chitosan composite material.
[0054] More specifically, the electrode is one of a glassy carbon electrode, a graphite electrode, a carbon electrode, and a carbon fiber electrode.
[0055] Preferably, the electrode is a glassy carbon electrode (GCE).
[0056] More specifically, with the electrode as the substrate, the titanium-doped lamellar FER molecular sieve immobilized chitosan composite material is used to modify the electrode (CS), and the modified electrode is an electrochemical sensor based on titanium-doped lamellar FER molecular sieve immobilized chitosan (also called CS / Ti / FER / GCE electrode in the present invention).
[0057] The titanium-doped layered FER molecular sieve immobilized chitosan composite material modified electrode has a significant electrocatalytic oxidation effect on rutin. During the electrochemical detection process, rutin undergoes oxidation reaction on the surface of the modified electrode to generate corresponding oxidation products. Due to the modification of the above composite material, the electrocatalytic activity of the electrode surface is improved, making the oxidation reaction of rutin easier to proceed, thereby improving the sensitivity and selectivity of the sensor for rutin detection.
[0058] In addition, the oxidation potential of rutin on the bare electrode is high and is easily interfered by other substances in the sample. After the electrode is modified with the above composite material, the oxidation potential of rutin can be reduced, so that rutin undergoes oxidation reaction at a lower potential, reducing the competitive reaction with other substances and improving the specificity of the sensor.
[0059] Therefore, the present invention adopts a titanium-doped layer FER molecular sieve immobilized chitosan composite material to modify the electrode. The modified electrode has an obvious catalytic oxidation effect on rutin, can significantly improve the sensitivity of rutin detection and increase the linear range of rutin concentration. The linear range of rutin detection reaches 0.1-10 μmol / L, the concentration detection range is wide, the detection limit is low, the sensitivity is high, the stability is good, and the repeatability and selectivity are high.
[0060] More specifically, the preparation method of the electrochemical sensor is:
[0061] The titanium-doped sheet FER molecular sieve immobilized chitosan composite material is prepared into a suspension, and then coated on the electrode surface to obtain the electrochemical sensor.
[0062] A three-electrode system comprises a reference electrode, a counter electrode and a working electrode, wherein the working electrode is the electrochemical sensor.
[0063] This three-electrode system can be used for accurate detection of rutin content in body fluids.
[0064] Specifically, the reference electrode is a saturated calomel electrode, and the counter electrode is a platinum wire electrode.
[0065] The present invention also protects the use of the titanium-doped lamella FER molecular sieve or the titanium-doped lamella FER molecular sieve-immobilized chitosan composite material or the electrochemical sensor or the three-electrode system in detecting rutin.
[0066] Compared with the prior art, the present invention has the following beneficial effects:
[0067] (1) The present invention discloses a novel template agent and a titanium-doped lamella FER molecular sieve synthesized by regulating a specific raw material ratio. The special long carbon chain of the template agent guides the lamella structure of the Na-FER molecular sieve, so that the FER molecular sieve has a smaller crystal structure. Micropores and mesopores are simultaneously generated during the preparation process, which greatly increases the specific surface area of the molecular sieve and improves the molecular sieve's adsorption performance for rutin.
[0068] (2) The titanium-doped lamellar FER molecular sieve prepared by the present invention has the conductivity of the molecular sieve enhanced by titanium doping, so that the molecular sieve exposes more active sites, thereby enhancing the catalytic performance of the molecular sieve, which is beneficial to the electrocatalytic reaction of rutin on the sensor.
[0069] (3) The present invention uses titanium-doped lamellar FER molecular sieve to immobilize chitosan composite modified electrode (GCE) and construct a rutin electrochemical sensor, which is used for rutin sheet detection and analysis. The results show that the obtained electrochemical sensor has a linear concentration range of 0.1 to 10 μmol / L for rutin detection, a wide concentration detection range, high detection sensitivity, accuracy, repeatability and selectivity, a low detection limit and good stability.
[0070] (4) The rutin electrochemical sensor prepared by the present invention is easy to operate and inexpensive, and can realize timely monitoring of rutin in food and medicine and is of great significance for preventing various related diseases. BRIEF DESCRIPTION OF THE DRAWINGS
[0071] Figure 1 H NMR spectrum of the template.
[0072] Figure 2 1 and 2 are SEM images of the lamellar FER molecular sieve and the titanium-doped lamellar FER molecular sieve in Example 1.
[0073] Among them, Figures (a), (b), (c), and (d) are lamellar FER molecular sieves, and Figures (e) and (f) are titanium-doped lamellar FER molecular sieves in Example 1; the magnification of Figure (a) is 5000 times, the magnification of Figure (b) is 10000 times, the magnification of Figure (c) is 30000 times, the magnification of Figure (d) is 60000 times, the magnification of Figure (e) is 10000 times, and the magnification of Figure (f) is 30000 times.
[0074] Figure 3(a) is the small angle X-ray diffraction pattern of lamellar FER molecular sieve at 0-5°, Figure 3 (b) is the X-ray diffraction pattern of the lamellar FER molecular sieve and the titanium-doped lamellar FER molecular sieve prepared in Example 1 at 5-40°.
[0075] Figure 4 The voltammetric curves of the CS / Ti / FER / GCE electrode (b) and the bare GCE electrode (a) prepared in Example 1 in a PBS solution of pH = 3 containing 50 μmol / L rutin.
[0076] Figure 5 The differential pulse voltammetry curves of the CS / Ti / FER / GCE electrode prepared in Example 1 in rutin standard solutions of different concentrations are shown in the figure. The inset is a statistical diagram of the linear relationship between the oxidation peak current and the concentration.
[0077] Figure 6 This is a statistical diagram of the data for verifying the selectivity of the CS / Ti / FER / GCE electrode prepared in Example 1 for rutin.
[0078] Figure 7 This is a statistical graph of the data for the reproducibility verification of rutin by the CS / Ti / FER / GCE electrode prepared in Example 1.
[0079] Figure 8 This is a statistical graph showing the stability of the CS / Ti / FER / GCE electrode prepared in Example 1 for rutin. DETAILED DESCRIPTION
[0080] The present invention is further described below in conjunction with examples. These examples are only used to illustrate the present invention and are not intended to limit the scope of the present invention. The experimental methods in the following examples that do not specify specific conditions are usually carried out according to conventional conditions in the art or according to the conditions recommended by the manufacturer; the raw materials, reagents, etc. used, unless otherwise specified, are all raw materials and reagents that can be obtained from commercial channels such as conventional markets. Any non-substantial changes and substitutions made by those skilled in the art on the basis of the present invention belong to the scope of protection claimed by the present invention.
[0081] Among them, the sources of raw materials used in the comparative examples and embodiments of the present invention are as follows: rutin standard samples were purchased from Maclean Co., Ltd., compound rutin tablets were purchased from World Trade Center Pharmaceutical (Jiangsu) Co., Ltd., chitosan was purchased from Maclean Co., Ltd., titanium dioxide was purchased from Myrel Co., Ltd., phosphate buffer solutions (PBS) of different pH values were prepared by Na2HPO4 and NaH2PO4 in different proportions, and a buffer solution of pH <5 was prepared by using NaH2PO4 and then using hydrochloric acid to adjust the pH. All reagents were analytically pure reagents, and the solutions were prepared with deionized water.
[0082] The structural formula of the carbon chain organic compound (i.e., template) used in the embodiment of the present invention is as follows:
[0083] NH2-C2H4-NH-(CH2) 12 -O-(p-C6H4)2-O-(CH2) 12 -NH-C2H4-NH2;
[0084] The above carbon chain organic compounds can be synthesized by the following method:
[0085] S1. Dissolve 10 mmol 4,4-diphenol in 80 ml anhydrous ethanol containing 20 mmol potassium hydroxide, add 60 mmol 1,12-dibromododecane, reflux at 80 ° C for 20 hours, filter while hot, wash with ethanol repeatedly 3 times and filter, collect the filtered product, and dry it in a vacuum oven at 50 ° C for 12 hours to obtain the precursor Br-(CH2) 12 -O-(p-C6H4)2-O-(CH2) 12 -Br.
[0086] S2. 20 mmol of the precursor and 250 mmol of ethylenediamine were mixed into an acetonitrile / toluene solution (25 ml each) with a volume ratio of 1:1, and stirred at 70°C in a N2 atmosphere for 10 hours to obtain the product. The product was washed with ether three times and then filtered. The filtered product was collected and dried in a vacuum oven at 50°C for 12 hours to obtain the template NH2-C2H4-NH-(CH2) 12 -O-(p-C6H4)2-O-(CH2) 12 -NH-C2H4-NH2, its relative molecular mass is 639.0214. Its NMR spectrum is as follows Figure 1 shown.
[0087] 1 The results of H NMR spectrum are as follows: 1 H NMR (400MHz, CDCl3), δ (ppm): δ7.45 (d, 4H, Ar-H), 6.94 (d, 4H, H-Ar-O), 3.98 ( t, 4H, -OCH2), 2.80 (t, 2H, -NH-), 2.75 (s, 8H, -N-(CH2)2-N-), 2.66 (t, 2H, -N- CH2), 2.60 (t, 2H, -N-CH2-), 1.79 (q, 4H, -NH2), 1.49 (s, 4H, -N-CH2-CH2), 1.4 7(s, 4H, Ar-O-(CH2)2-CH2), 1.44(s, 4H, Ar-O-CH2-CH2), 1.28(s, 28H, -CH2-).
[0088] It can be seen from the nuclear magnetic resonance spectrum that the template of the present invention has peaks at the key peak positions, indicating that it has been successfully synthesized; there are also a small amount of miscellaneous peaks in the figure, which may be caused by a small amount of impurities in the sample.
[0089] A lamellar FER molecular sieve, the preparation method of which comprises the following steps:
[0090] S1. Take 16g of deionized water, add 0.128g of sodium hydroxide and 0.308g of sodium aluminate, stir for 20min, then add 5.72g of silica sol and 0.688g of the above template, mix and stir thoroughly, and stir magnetically at 25°C for 10h to obtain aluminosilicate gel. The molar ratio of sodium aluminate, sodium hydroxide, silica sol, water and template is 1:0.85:7.6:235:0.28.
[0091] S1. The aluminosilicate gel obtained in step S1 is transferred to a Teflon-lined stainless steel autoclave, subjected to hydrothermal reaction at 180°C for 10 days, centrifuged at 9000 r / min for 3 min, washed, and the product is collected, dried at 120°C for 12 h, and then calcined at 550°C for 6 h to obtain a lamellar FER molecular sieve.
[0092] Example 1
[0093] This embodiment provides a titanium-doped lamella FER molecular sieve, and the preparation method thereof comprises the following steps:
[0094] S1. Take 16g of deionized water, add 0.128g of sodium hydroxide and 0.308g of sodium aluminate, stir for 20 minutes, then add 5.72g of silica sol and 0.688g of template, mix and stir thoroughly to obtain aluminosilicate gel. The molar ratio of sodium aluminate, sodium hydroxide, silica sol, water and template is 1:0.85:7.6:235:0.28.
[0095] S2. TiO2 is mixed with the aluminosilicate gel obtained in step S1, and magnetically stirred at 25°C for 10 hours, with the mass ratio of titanium dioxide to aluminosilicate gel being 1:200. The mixture is transferred to a Teflon-lined stainless steel autoclave, and hydrothermally reacted at 180°C for 10 days. The product is washed and collected after centrifugation at 9000 r / min for 3 minutes, and dried at 120°C for 12 hours, and then calcined at 550°C for 6 hours to obtain a titanium-doped lamellar FER molecular sieve.
[0096] This embodiment provides a titanium-doped lamellar FER molecular sieve immobilized chitosan composite material, and the preparation method thereof comprises the following steps:
[0097] 10 mg of titanium-doped lamellar FER molecular sieve powder was dispersed in 10 mL of an aqueous solution of acetic acid and chitosan, and ultrasonically dispersed for 30 minutes to obtain a suspension of the titanium-doped lamellar FER molecular sieve-immobilized chitosan composite material.
[0098] This embodiment provides an electrochemical sensor, and the preparation method thereof comprises the following steps:
[0099] S1. A glassy carbon electrode with a diameter of 3 mm was polished with Al2O3 polishing powder, and then ultrasonically cleaned in deionized water and anhydrous ethanol for 30 min respectively, and dried at room temperature;
[0100] S2. Take 10 μL of the suspension of titanium-doped lamellar FER molecular sieve immobilized chitosan composite material and drop it onto the treated glassy carbon electrode (GCE), and air-dry it naturally to obtain an electrochemical sensor based on titanium-doped lamellar FER molecular sieve immobilized chitosan (also known as CS / Ti / FER / GCE electrode).
[0101] Example 2
[0102] This embodiment provides a titanium-doped lamellar FER molecular sieve, and its preparation method is the same as that of Example 1, except that the amount of template added in step S1 is 0.917 g, and the molar ratio of sodium aluminate, sodium hydroxide, silica sol, water and template is 1:0.85:7.6:235:0.37.
[0103] This embodiment provides a titanium-doped lamellar FER molecular sieve immobilized chitosan composite material and an electrochemical sensor, and the preparation method thereof is the same as that of Embodiment 1, except that the titanium-doped lamellar FER molecular sieve of this embodiment is used.
[0104] Example 3
[0105] This embodiment provides a titanium-doped lamellar FER molecular sieve, and its preparation method is the same as that of Example 1, except that the amount of template added in step S1 is 1.147 g, and the molar ratio of sodium aluminate, sodium hydroxide, silica sol, water and template is 1:0.85:7.6:235:0.47.
[0106] This embodiment provides a titanium-doped lamellar FER molecular sieve immobilized chitosan composite material and an electrochemical sensor, and the preparation method thereof is the same as that of Embodiment 1, except that the titanium-doped lamellar FER molecular sieve of this embodiment is used.
[0107] Example 4
[0108] This embodiment provides a construction of a three-electrode system: a three-electrode system is adopted, with the titanium-doped sheet FER molecular sieve immobilized chitosan electrochemical sensor obtained in Example 1 as the working electrode, the reference electrode as a saturated calomel electrode, and the counter electrode as a platinum wire electrode.
[0109] Comparative Example 1
[0110] This comparative example provides a FER molecular sieve, and the template used is ethylenediamine. The preparation method thereof is referenced in: Chen Xiaoxin. Hydrothermal synthesis and characterization of ferrierite in two different systems [J]. Chemical Education, 2015, 36(18): 21-25.
[0111] The reaction process is as follows: add 7.16g deionized water and 1mL ethylenediamine to a 50mL plastic beaker, mix evenly under magnetic stirring, and stir for 5min; add 0.01g sodium hydroxide and 0.14g sodium aluminate to the above reaction system respectively, and stir magnetically for 30min; slowly add 1.3mL silica sol (SiO2 content 40%) to the above reaction system under magnetic stirring conditions, and continue stirring for 1h. The composition of the reaction sol is SiO2·0.15NaAlO2·0.021NaOH·1.33ethylenediamine·39.60H2O. The reaction mixture in the above 50mL plastic beaker is transferred to a reactor equipped with a polytetrafluoroethylene reactor liner, and after tightening the reactor, it is placed in a 180℃ oven for heating and crystallization for 240h. After the product treatment crystallization reaction is completed, the reactor is cooled to room temperature, the product is filtered, washed with deionized water until the pH is neutral, and then naturally dried to obtain the product, which is calcined at 550°C for 6h and then automatically cooled to room temperature.
[0112] Performance Testing
[0113] 1. Characterization of molecular sieve performance
[0114] (1) SEM test
[0115] The flake FER molecular sieve and the titanium-doped flake FER molecular sieve prepared in Example 1 were measured using a Merlin field emission scanning electron microscope from Zeiss, Germany. Figure 2 As shown, the FER molecular sieve synthesized by the homemade template in the present invention has an obvious flake structure. Figure 2 (e) and (f) show that the morphology of the FER molecular sieve does not change after being doped with titanium sheets.
[0116] (2) X-ray diffraction test
[0117] The flake FER molecular sieve and the titanium-doped flake FER molecular sieve prepared in Example 1 were characterized using a D8 Advance X-ray diffractometer from Bruker, Germany. Figure 3As shown, the standard diffraction peak of FER molecular sieve is shown when 2θ is 5-40°, and there is a diffraction peak when 2θ is 0-5°, indicating that the layered FER molecular sieve obtained by the present invention has a mesoporous structure. And by comparing the FER molecular sieve and the titanium-doped layered FER molecular sieve with the FER standard card, the XRD of the titanium-doped layered FER molecular sieve has no obvious change, indicating that titanium is well dispersed in the molecular sieve framework.
[0118] (3) BET test
[0119] The lamellar FER molecular sieve, the titanium-doped lamellar FER molecular sieve prepared in Example 1, and the FER molecular sieve prepared in Comparative Example 1 were characterized using American Micromeritics ASAP 2460. The results are shown in Table 1.
[0120] Table 1 Molecular sieve pore structure parameters
[0121]
[0122] As shown in Table 1, N2 adsorption and desorption isothermal experiments were carried out on the flaky FER molecular sieve and the titanium-doped flaky FER molecular sieve prepared in Example 1, and the data of the FER molecular sieve prepared using ethylenediamine as the template obtained in Comparative Example 1 were compared. The results are shown in Table 1, and it can be seen that the flaky FER molecular sieve synthesized by the homemade template has a larger specific surface area, reaching 312.3327 m 2 ·g -1 301m larger than ethylenediamine as template for preparing FER molecular sieve 2 ·g -1 , and the pore volume of the lamellar molecular sieve is also significantly higher than that of the conventional molecular sieve, and the FER molecular sieve prepared by the present invention has more mesopores. After the titanium-doped lamellar FER molecular sieve, the specific surface area is slightly reduced, indicating that titanium has successfully entered the molecular sieve framework, and the titanium-doped lamellar FER molecular sieve has a large specific surface area and a high adsorption capacity, which is conducive to the adsorption of rutin molecules and the rapid catalytic reaction.
[0123] 2. Performance determination of titanium-doped lamellar FER molecular sieve immobilized chitosan electrochemical sensor
[0124] (1) Cyclic voltammetry test
[0125] The three-electrode system of Example 5 was tested by cyclic voltammetry using a CHI660E electrochemical workstation produced by Shanghai Hua Instrument Co., Ltd. The results are as follows: Figure 4As shown, in a PBS solution containing 50 μmol / L rutin, the titanium-doped lamellar FER molecular sieve immobilized chitosan electrochemical sensor (b) has a higher oxidation peak than the lamellar FER molecular sieve immobilized chitosan electrochemical sensor (a) under a potential of 0.52 V, indicating that the titanium-doped lamellar FER molecular sieve electrode has a better electrochemical response to rutin.
[0126] (2) Differential pulse voltammetry test
[0127] In a three-electrode system, differential pulse voltammetry was performed on rutin standard solutions with different concentrations, such as Figure 5 As shown in the figure, within the potential range of 0.2-0.8V, when the concentration of rutin changes from 0.1 to 10 μmol / L, the peak current increases significantly with the increase of concentration. The square root of the response current of the catalytic reaction is linearly related to the square root of the rutin concentration. The relationship between the response current and the rutin concentration is Y=0.20884X+6.25155, and the correlation coefficient is R 2 =0.9912, and the detection limit is 0.1 μmol / L. The above results show that the titanium-doped sheet FER molecular sieve immobilized chitosan electrochemical sensor obtained by the present invention has a wide detection linear range (0.1-10 μmol / L) and a low detection limit (0.1 μmol / L), and can accurately detect rutin. The detection range of rutin detected by high performance liquid chromatography is usually 5.0-20.0 μg / mL, and the detection range of rutin detected by spectrophotometry is usually 0.0022 mg / mL-0.156 mg / mL. The titanium-doped sheet FER molecular sieve immobilized chitosan electrochemical sensor obtained by the present invention has a wide detection linear range (0.1-10 μmol / L), and the detection limit is much lower than the methods used on the market. Therefore, the present invention can meet the detection needs for low rutin states.
[0128] (3) Selectivity, reproducibility and stability testing
[0129] In the three-electrode system, an interfering substance was added to the PBS solution containing 10 μmol / L rutin and then tested. The interfering substance was Cu 2+ , K + 、Zn 2+ , L-tyrosine, L-tryptophan, glucose and riboflavin, where the interfering substance is 50 times the concentration of rutin, thereby verifying the selectivity of the titanium-doped layer FER molecular sieve immobilized chitosan electrochemical sensor (i.e., CS / Ti / FER / GCE electrode) obtained in Example 1. The results are as follows Figure 6 As shown, after adding interfering ions with a concentration of 50 times that of the PBS solution of rutin, the current does not change much, indicating that the titanium-doped layer FER molecular sieve immobilized chitosan electrochemical sensor obtained in the present invention has good selectivity.
[0130] The rutin solution was measured 6 times at different times using the same CS / Ti / FER / GCE electrode obtained in Example 1. The results are as follows: Figure 7 As shown, the current values obtained 6 times are basically similar, indicating that the electrode has good reproducibility.
[0131] Figure 8 This is a statistical diagram of the stability verification of rutin by the CS / Ti / FER / GCE electrode prepared in Example 1. The test time is 40 hours, and the current values are basically similar within 40 hours, which shows that the electrode has good stability.
[0132] (4) Accuracy test
[0133] In the three-electrode system, the actual compound rutin tablets were diluted with buffer solution instead of the rutin standard solution for detection, and the results are shown in Table 1. The sample concentration in Table 1 is calculated and prepared according to the content of rutin in each tablet indicated on the instructions of the compound rutin tablets. The rutin sample concentration after the actual compound rutin tablets were diluted was 10 μmol / L. The recovery rate of rutin concentration was between 93.4% and 96.7%, and the RSD was 5.4%, which shows that the test accuracy is good and can meet the test requirements. This also shows that the CS / Ti / FER / GCE electrode obtained by the present invention has good rutin detection performance.
[0134] Table 2
[0135]
[0136] The performance characterization results of the electrochemical sensors obtained in Examples 2 and 3 are substantially the same as those in Example 1, and will not be described in detail herein.
[0137] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A carbon chain organic compound, characterized in that The structural formula of the organic compound is: NH2-C2H4-NH-(CH2) n -O-(p-C6H4)2-O-(CH2) n -NH-C2H4-NH2; wherein n is 10 to 16.
2. Use of the organic compound as claimed in claim 1 in the preparation of FER molecular sieve.
3. A titanium-doped lamellar FER molecular sieve, characterized in that: The organic compound according to claim 1 is used as a template and prepared by a hydrothermal method.
4. The titanium-doped FER molecular sieve according to claim 3, characterized in that: The method for preparing the titanium-doped lamellae FER molecular sieve comprises the following steps: S1. Mixing an aluminum source, an alkali source, a silicon source, a template and water to obtain an aluminosilicate gel; S2. mixing the aluminosilicate gel with a titanium source, hydrothermally heating, and calcining to obtain the titanium-doped lamellar FER molecular sieve; The mass ratio of the titanium source to the aluminosilicate gel is 1:100-500.
5. The titanium-doped FER molecular sieve according to claim 4, characterized in that: The molar ratio of the aluminum source, the alkali source, the silicon source, the template and water is 1: (0.4-20): (1-40): (0.02-6): (20-800).
6. The titanium-doped FER molecular sieve according to claim 3, characterized in that: The hydrothermal temperature is 130-200°C.
7. A titanium-doped lamellar FER molecular sieve immobilized chitosan composite material, characterized in that: The preparation method comprises the following steps: The titanium-doped lamellar FER molecular sieve according to any one of claims 3 to 6 is dispersed in an aqueous solution of acetic acid and chitosan to obtain the titanium-doped lamellar FER molecular sieve immobilized chitosan composite material.
8. An electrochemical sensor, characterized in that The electrochemical sensor comprises an electrode and the titanium-doped lamellae FER molecular sieve immobilized chitosan composite material as claimed in claim 7.
9. A three-electrode system, characterized in that: The three-electrode system comprises a reference electrode, a counter electrode and a working electrode, and the working electrode is the electrochemical sensor according to claim 8.
10. Use of the titanium-doped lamellar FER molecular sieve according to any one of claims 3 to 6, or the titanium-doped lamellar FER molecular sieve immobilized chitosan composite material according to claim 7, or the electrochemical sensor according to claim 8, or the three-electrode system according to claim 9 in detecting rutin.
Citation Information
Patent Citations
Synthesis method of ferrierite (FER) zeolite molecular sieve and obtained FER zeolite molecular sieve
CN102530979A
Preparation method of template agent and preparation method of MFI molecular sieve supporting titanium
CN107285335A
Mesoporous and microporous MFI type nano molecular sieve with flaky pastry-shaped morphology and preparation method and application thereof
CN108002402A
Preparation method of adsorbent for purifying hydrogen peroxide solution, and purification method of hydrogen peroxide
CN108499525A
High-activity hierarchical-pore titanium-silicon molecular sieve as well as preparation method and application thereof
CN108821304A
Cited By
MWW molecular sieve composite material with high adsorption capacity and conductivity, electrochemical sensor and preparation method and application of MWW molecular sieve composite material
CN121551056A
A mww molecular sieve composite material with high adsorption capacity and conductivity, an electrochemical sensor and a preparation method and application thereof
CN121551056B